Research on evaluation and influencing factors of regional ecological efficiency from the perspective of carbon neutrality. (15th September 2021) - Tan, Junlan; Wang, Rong
Abstract: Carbon neutrality is an important environmental management tool to deal with the global greenhouse effect. Addressing climate change is an important starting point for promoting the high-quality development of China's economy and the construction of ecological civilization, as well as an important area for participating in global governance and adhering to multilateralism. In this paper, from the perspective of carbon neutrality, taking China's Jiangsu Province as an example, the super-efficiency DEA model is selected to measure the level of ecological efficiency in Jiangsu, and on this basis, the Tobit model is used to verify the main factors affecting regional ecological efficiency. The results are as follows: (1) The regional eco-efficiency in Jiangsu shows a trend of decreasing from south to north, with obvious phenomenon of "club convergence", with significant spatial correlation and agglomeration. (2) The industrial structure is negatively related to the regional eco-efficiency of Jiangsu regions; Energy consumption structure has a positively impact in southern Jiangsu, but negatively in central and northern Jiangsu; FDI has a positively impact in central and northern Jiangsu, but negatively in southern Jiangsu; Regional economic development has a positively impact in southern and northern Jiangsu, but negatively in central Jiangsu; The progress in the technological level has positive effects on the eco-efficiency of all regions of Jiangsu. The final paper puts forward some suggestions based on the carbon neutral target Provide theoretical reference for achieving the goal of carbon neutrality. Highlights: Construct an regional ecological efficiency evaluation index system. Use super-DEAmethod to measure ecological efficiency level. Study from the perspective of carbon neutrality. Propose a reference for achieving carbon neutrality.